Reorientation of Rural Development as a Base for Improving Land Ownership Distribution at Farmer Level - Jamal, Erizal (+622518321746, 2013)
The problem of unbalanced land distribution at farm level in Â Â Â Indonesia has hampered many efforts to improve rural livelihoods.Â Â Â Several development programs that have been implemented by Â Â Â the government have not been fully benefitted by smallholders Â Â Â due to various reasons, and in many cases this condition even Â Â Â further widen inequality, because onlyÂ landowners who are able Â Â Â to take advantage the vast range of opportunities created through Â Â Â the programs. In the future, a reorientation of rural development Â Â Â is needed with more emphasis on improving farmersâ access to Â Â Â information, capital, technology, and their capacity to take Â Â Â advantage of opportunities that are locally available. Reorientation Â Â Â of rural development will be initiated with changes of the Â Â Â approaches in the planning and implementation of development, Â Â Â with emphasis on the development of diverse types of businesses, Â Â Â as well as capacity building of the community to take advantage Â Â Â of the growing local opportunities. These efforts need to be Â Â Â supported by the implementation of rural development with an Â Â Â integrated approach, through a strong cooperation at the district Â Â Â level under the coordination of District Development Planning Â Â Â Agency. Rural development planning should be directed to two Â Â Â main issues. Firstly, open up new business opportunities, especially Â Â Â those non-based land activities. Secondly, build the community Â Â Â capacity to capture the existing business opportunities. The Â Â Â technologies being developed should be neutral with respect to Â Â Â farmers land ownership, and the technology dissemination is Â Â Â supposed to be proportional in order to reach all levels of farmers.Â Â Â